Culture, morality and individual differences: comparability and incomparability across species. (26th February 2018) - Saucier, Gerard
Abstract : Major routes to identifying individual differences (in diverse species) include studies of behaviour patterns as represented in language and neurophysiology. But results from these approaches appear not to converge on some major dimensions. Identifying dimensions of human variation least applicable to non-human species may help to partition human-specific individual differences of recent evolutionary origin from those shared across species. Human culture includes learned, enforced social-norm systems that are symbolically reinforced and referenced in displays signalling adherence. At a key juncture in human evolution bullying aggression and deception-based cheating apparently became censured in the language of a moral community, enabling mutual observation coordinated in gossip, associated with external sanctions. That still-conserved cultural paradigm moralistically regulates selfish advantage-taking, with shared semantics and explicit rules. Ethics and moral codes remain critical and universal components of human culture and have a stronger imprint in language than most aspects of the currently popular Big-Five taxonomy, a model that sets out five major lines of individual-differences variation in human personality. In other species (e.g. chimpanzees), human observers might see apparent individual differences in morality-relevant traits, but not because the animals have human-analogue sanctioning systems. Removing the moral dimension of personality and other human-specific manifestations (e.g. religion) may aid in identifying those other bases of individual differences more ubiquitous across species. This article is part of the theme issue 'Diverse perspectives on diversity: multi-disciplinary approaches to taxonomies of individual differences'.